INVESTIGATION OF ANXIETY AMONG PATIENTS UNDERGOING IMPACTED WISDOM TOOTH EXTRACTION IN PESHAWAR - Dr. Junaid Hamza; Dr. Malik Farhan Hameed; Dr. Anees Ur Rehman; Dr. Syeda Addan Azam; Dr. Muhammad Umair; Dr. Farrukh Ali (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The study aimed to investigate the prevalence and intensity of anxiety among patients undergoing impacted wisdom tooth extraction in Peshawar, Pakistan. A cross-sectional survey was conducted among 250 patients in dental clinics across Peshawar, utilizing the Modified Dental Anxiety Scale (MDAS). The findings revealed that a significant portion of the population experienced moderate to severe anxiety, with a higher prevalence in women and younger individuals. Strategies for reducing dental anxiety, particularly preoperative counseling and anxiety management techniques, are discussed as important considerations for improving patient outcomes in dental care.